The Understanding of Workplace Spirituality among a Group of Human Resource Managers: Meaning, Influencing Factors and Practices - Gözdegül Başer; Rüya Ehtiyar (Anı Publishing, 2019)
The purpose of this paper was to find out how workplace spirituality was understood by a group of human resource managers from Turkey and how it was practised in their companies. The research methodology was qualitative, and the study followed a phenomenological research design. A focus group interview method was used to collect the data. The data were analysed using content analysis. Three main themes and their sub-themes are reported. The findings indicated that the participants had different understandings and definitions of workplace spirituality. Workplace spirituality was understood as being related to organizational values, commitment, loyalty, trust, support, integration and identification, and also to participatory management and support from senior management. The main factors influencing workplace spirituality were participatory management, touching the heart, well-established organizational communication, reciprocity, respect for employees and their acceptance as part of the family, appreciation and motivation, the giving of rewards and official rights to employees and, finally, cultural values. The practices related to workplace spirituality were different, but they were mostly aimed at a stronger organizational communication and commitment. The study contributes to the understanding of workplace spirituality and forms a basis for further research.